2015
DOI: 10.1371/journal.pone.0144411
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-Emergent Phonology in the Amplitude Envelope of Child-Directed Speech

Abstract: When acquiring language, young children may use acoustic spectro-temporal patterns in speech to derive phonological units in spoken language (e.g., prosodic stress patterns, syllables, phonemes). Children appear to learn acoustic-phonological mappings rapidly, without direct instruction, yet the underlying developmental mechanisms remain unclear. Across different languages, a relationship between amplitude envelope sensitivity and phonological development has been found, suggesting that children may make use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
188
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(213 citation statements)
references
References 78 publications
18
188
0
7
Order By: Relevance
“…Further, recent analyses of the amplitude modulation structure of Australian English infant-directed speech (IDS) show a modulation peak at 2 Hz, the “prosodic rate” (see Leong, Kalashnikova, Burnham, & Goswami, 2014), not at 4–6 Hz, the modulation peak found for adult-directed speech (ADS, see Greenberg, Carvey, Hitchcock, & Chang, 2003). These different modulation peaks imply that early in development, accurate encoding of low frequency envelopes (delta band) could play a crucial role in setting up a phonological lexicon (Leong & Goswami, 2015). Infants and young children who are relatively insensitive to low-frequency envelope information would benefit less from the prosodic information in IDS as they build their lexical phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent analyses of the amplitude modulation structure of Australian English infant-directed speech (IDS) show a modulation peak at 2 Hz, the “prosodic rate” (see Leong, Kalashnikova, Burnham, & Goswami, 2014), not at 4–6 Hz, the modulation peak found for adult-directed speech (ADS, see Greenberg, Carvey, Hitchcock, & Chang, 2003). These different modulation peaks imply that early in development, accurate encoding of low frequency envelopes (delta band) could play a crucial role in setting up a phonological lexicon (Leong & Goswami, 2015). Infants and young children who are relatively insensitive to low-frequency envelope information would benefit less from the prosodic information in IDS as they build their lexical phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it remains unclear which modulations (time-scales), are the most important relating acoustic information with phonological. Investigating this issue, Leong and Goswami [15], studied how acoustic spectrotemporal structure is related to the linguistic phonological structure of speech, using amplitude demodulation in three time-scales, i.e, prosodic stress, syllable and onset-rime unit (phonemes) levels.…”
Section: Introductionmentioning
confidence: 99%
“…The spectro-temporal features [28][29][30][31][32][33] at these timescales highly correlated speech intelligibly and ability to understand or comprehend. Studies reported impairments in short time scales [34][35][36] and long time scales [37,38,40] on the speech signal of children with neurodevelopmental disorders. Most of these studies focused on the impairments in the spectro-temporal features in the speech of subjects with intellectual disabilities but none has developed the classification model for these groups based on features encoded at multiple timescales.…”
Section: Introductionmentioning
confidence: 99%